Characterization, molecular and pathogenicity of Metarhizium huainamdangense isolated from Dumoga against the corn leafhopper Peregrinus maidis - PARLUHUTAN SIAHAAN; MAGFIRA LANGANAWA; ROWLAND ERVAN RUSFANDI MANGAIS (Society for Indonesian Biodiversity, 2025)
Abstract. Siahaan P, Langanawa M, Mangais RER. 2025. Characterization, molecular and pathogenicity of Metarhizium huainamdangense isolated from Dumoga against the corn leafhopper Peregrinus maidis. Biodiversitas 26: 6111-6119. The corn leafhopper (Peregrinus maidis) is a major pest of maize, causing significant yield losses and threatening sustainable production. Reliance on chemical pesticides has led to resistance and environmental risks, creating a demand for eco-friendly alternatives. Entomopathogenic fungi, particularly Metarhizium spp., have shown strong potential as biological control agents. This study characterized and evaluated the pathogenicity of a local Metarhizium isolate from West Dumoga, North Sulawesi, Indonesia. Morphological observations confirmed colony and conidial traits typical of Metarhizium. Molecular identification through ITS sequencing placed the isolate within the Metarhizium huainamdangense clade with >98% similarity. Conidial density reached 1.39 × 10? conidia/mL with 100% germination after 24 hours, indicating strong physiological fitness. Pathogenicity assays against P. maidis demonstrated concentration- and time-dependent mortality, with up to 100% mortality at 10? conidia/mL by day 14. However, the high LC?? (1 × 10?. conidia/mL) and LT?? (>8.5 days) values indicate relatively low virulence compared with other Metarhizium species. This study confirms the Dumoga local isolate as Metarhizium huainamdangense and has potential as a promising biocontrol agent with formulation optimization to improve field effectiveness in integrated pest management.